A Study on the Spatial Morphological Evolution and Driving Factors of Coral Islands and Reefs in the South China Sea Based on Multi-Source Satellite Imagery - Fengyu Li; Wenzhou Wu; Peng Zhang; Bingyue Zhang; Fenzhen Su (Journal of Marine Science and Engineering)
The spatial morphology of coral islands and reefs is a fundamental physical and ecological attribute that reflects the developmental and evolutionary processes of coral islands and reefs. The spatial morphology of coral islands and reefs in the South China Sea is highly dynamic. Understanding the evolutionary trends of the spatial morphology of these coral islands and reefs is crucial for their sustainable development and utilization. This study proposes a set of stability evaluation indicators for reef spatial morphology and conducts a systematic analysis of the spatial morphological changes in coral islands and reefs in the South China Sea over the past 15 years, based on 96 satellite images. Additionally, the driving factors behind these changes are explored and discussed. The results indicate the following: (1) The spatial morphology of the Xisha islands and reefs exhibits more significant changes compared to the Nansha islands and reefs. Although both the Xisha and Nansha islands and reefs areas are increasing, the area change in Xisha is 1.3 times greater than that in Nansha. (2) The spatial morphology of the Xisha islands and reefs is shifting in all directions, while the Nansha islands and reefs show a more pronounced northwestward movement. (3) Both the Xisha and Nansha islands and reefs show an overall growth trend, with the growth rate of the Xisha islands and reefs being faster than that of the Nansha islands and reefs. The average growth rate of the Xisha islands and reefs is 1.77 times that of the Nansha islands and reefs. This research provides significant scientific evidence for the protection and resource management of coral islands and reefs in the South China Sea.